Extragastrointestinal Stromal Tumor Arising in the Pancreas: A Case Report with a Review of the Literature - Padhi, Somanath; Kongara, Ravikanth; Uppin, Shantveer G; Uppin, Megha S; Prayaga, Aruna K; Challa, Sundaram; Nagari, Bheerappa; Regulagadda, Shastry A (JOP. Journal of the Pancreas, 2010)
Context Extragastrointestinal stromal tumors arising in the pancreas are extremely rare. To date, only eight cases have been reported in the literature. Case report A 42-year-old female patient presented with gradually increasing abdominal pain of 6-month duration. Computerized tomography scan of the abdomen demonstrated a solid cystic mass in the body and tail of the pancreas. En-block R0 resection of the mass with distal pancreatectomy, splenectomy and left hemicolectomy was carried out following a radiological diagnosis of a malignant cystic neoplasm of the pancreas. Histopathological and immunohistochemical findings of the lesion were consistent with a gastrointestinal stromal tumor. Conclusion Extragastrointestinal stromal tumor of the pancreas, though rare, should be considered in the differential diagnosis of the more common cystic lesions at this site. Image: Large lobulated mass in relation to the body and tail of the pancreas.